'Born from a Woman': Unveiling the Marian Mystery beneath Paul's Allegory in Galatians 4. (November 2022) - Clarke, Kevin M.
Does Paul of Tarsus have a Mariology? Patristic exegetes and the liturgical tradition have latched onto his one obvious implication of Mary's place in the Christian mystery, that is, 'born from a woman' in Galatians. While this essay explores the case against a Mariological reading of Gal 4:4, it ultimately shows through plausible philological evidence that Paul intentionally refers to none other than Mary in 4:4. Sonship and motherhood are also taken up and further developed in his famous allegory equating the 'two women' of the Abrahamic narrative to 'two covenants.' But how many women are there in Galatians 4? The only ones named are Hagar and 'the Jerusalem above, ' while Sarah and Mary fade unmentioned into the silence of Pauline mystery. This essay unveils some further potential Mariological connections to be found in these women, focusing especially on the development of 'law, ' 'slave, ' 'woman, ' 'son, ' 'promise, ' and 'heir.'